Dietary Chitosan Oligosaccharide Supplementation Improves Meat Quality by Improving Antioxidant Capacity and Fiber Characteristics in the Thigh Muscle of Broilers - Ruixia Lan; Yuchen Wang; Haoxuan Wang; Jia Zhang (MDPI AG, 2024)
This study investigated the effects of dietary chitosan oligosaccharide (COS) supplementation on meat quality, antioxidant capacity, and muscle fiber characteristics in the thigh muscle of broilers. The results showed that dietary COS supplementation decreased shear force and increased crude protein content and nutritional value in the thigh muscle, while decreasing the content of C16:0, C18:0, and total saturated fatty acids. Dietary COS supplementation increased free radical scavenging activity, antioxidant enzyme activity, and antioxidant enzyme-related gene expression. Additionally, COS promoted MyHCI while decreasing MyHCIIb mRNA expression levels. The myofiber transformation was associated with upregulated gene expression of CaN, NFATc1, MyoD, and SIRT1. Together, the results of this study demonstrate that dietary COS supplementation improves meat quality, nutritional value, antioxidant capacity, and myofiber transformation to more oxidative muscle fibers in the thigh muscle of broilers when its supplemental level is 400 mg/kg.